Thoracic splenosis: Precision medicine can prevent thoracic surgery - Nathan Harb; Julia Fattore; Mayuran Saththianathan; Stephen Parsons (Respirology Case Reports)
Abstract Thoracic splenosis is a rare condition referring to the auto‐transplantation of splenic tissue into the thoracic cavity following splenic trauma. We present a case of thoracic splenosis in a 62‐year‐old man who at the age of 17 suffered three gunshot wounds to the posterior thorax and abdomen, requiring a splenectomy and intercostal catheter insertion. In 2007, he underwent a thoracotomy and biopsy of a left sided pulmonary mass which was complicated by a haemothorax requiring an emergent return to theatre and rib resection to achieve haemostasis. The biopsy revealed granulation tissue. In 2023, Technetium‐99m (Tc‐99m) heat‐damaged erythrocyte scintigraphy confirmed the diagnosis of thoracic splenosis. This case highlights the importance of recognizing this uncommon condition to prevent unnecessary investigation, as well as the use of Tc‐99m heat‐damaged erythrocyte scintigraphy to confirm the diagnosis.